The Analisis Aktivitas Antioksidan dan Mutu pada Teh Herbal Daun Keji Beling (Strobilanthes crispus BI) - Naifatun Irbah; Esi Emilia; Dina Ampera; Risti Rosmiati; Nila Reswari Haryana (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
This study aims to determine the drying temperature of keji beling leaf herbal tea which is preferred by panelists as well as its nutritional content, pottasium and antioxidant activity content. The research design used was an experimental study using a completely randomized design (CRD) method with a single factor, the drying temperature of keji beling leaf which was carried out with 4 treatments, P1 = 35°C, P2 = 45°C, P3 = 55°C, and P4 = 65°C which was dried for 150 minutes each using a dehydrator. The results of the study were analyzed using the Kruskal Wallis test method with the Mann-Whitney follow-up test. Determination of the best herbal tea was chosen based on the highest average value for each parameter. Based on the research results, the chosen treatment was P3 with a drying temperature of 55°C. The nutritional content of keji beling leaf herbal tea treated with a drying temperature of 55°C is potassium (21,8 mg/100 g), water content (12%), water extract content (2,92%), ash content (14,8%), water soluble ash content (0,37%), acid insoluble ash content (0,32%), ash alkalinity (63,1 ml NaOH/100 g), crude fiber (34,6%), and polyphenols (7,67%). Antioxidant activity based on the IC50 value is 106,3570 ppm.